2015
DOI: 10.1249/mss.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Femur Rotation Increases Patella Cartilage Stress in Females with Patellofemoral Pain

Abstract: The finding of elevated hydrostatic pressure and octahedral shear stress with internal rotation of the femur supports the premise that females with PFP who exhibit abnormal hip kinematics may be exposed to elevated patellofemoral joint stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 33 publications
2
38
1
1
Order By: Relevance
“…Our results support Liao et al series reporting higher patella cartilage stresses on the lateral facet of the patella after 5° and 10° of femoral rotation. [12]. Thus, Lee et al reported changes in kinematic of the PF joint with increased quadriceps muscle strain and increased pressure over the patellar facet at the contralateral side of the rotational deformity [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support Liao et al series reporting higher patella cartilage stresses on the lateral facet of the patella after 5° and 10° of femoral rotation. [12]. Thus, Lee et al reported changes in kinematic of the PF joint with increased quadriceps muscle strain and increased pressure over the patellar facet at the contralateral side of the rotational deformity [13].…”
Section: Discussionmentioning
confidence: 99%
“…PF changes in axial alignment are clinically relevant, especially for anterior knee pain and patellar instability [4,6,12]. However, the influence of stress distribution in anterior pain is controversial, because of the participation of the involved biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, compensatory behavior to accommodate for PFP may have effect on the tibiofemoral joint, as a result of its horizontal orientation, through axial compression (Powers et al, 1999). On the other hand, loading rate would not have strong effects on the patellofemoral joint by nature of its vertical alignment and the fact that patellofemoral compression is primarily dependent on the magnitude of quadriceps force (Maquet, 1984;Powers et al, 1999) and the femur orientation (Liao et al, 2015). Additionally, reduced knee flexion angles in both asymptomatic individuals and individuals with tibiofemoral osteoarthritis have also been linked with a more rapid increase in the ground reaction forces and greater rates of lower limb loading, which make the tibiofemoral joint especially susceptible to disease development and/or progression through increased axial compression and impulse loading (Cook et al, 1997;Mündermann et al, 2005;Radin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…20 Recruiting these muscles would prevent internal rotation of the hip, which has a deleterious effect on patello-femoral mechanics of the knee. 21 Alternatively, the gluteus medius is damaged during a lateral approach to the hip. As mentioned previously, this muscle is a powerful external rotator of the hip.…”
Section: Discussionmentioning
confidence: 99%